Optimizing Brain-Computer Interfaces for Methampetamine Use Disorder through Quantitative Electroencephalography (QEEG) and Transcranial Doppler Analysis: Article Review - Caroline, Maria; Syahrul, Syahrul; Tugasworo, Dodik; Retnaningsih, Retnaningsih; Juswanto, Gerard (Syntax Corporation Indonesia, 2024)
A Brain-Computer Interface (BCI) is a system that allows a person to control external devices using only their brain activity. It works by translating brain signals into commands that can be understood by a computer. Several lines of evidence demonstrated the deleterious effect of methamphetamine (MA) on neurological and psychological functions. The use of amphetamines, such as MA, is associated with cerebrovascular complications such as cerebrovascular accidents (CVA) ,hemorrhage, hypoxic damage and vasculitis. Interestingly, while changes to cerebral blood flow (CBF) in response to acute amphetamine exposure have been reported. Transcranial Color Doppler (TCCD) is a non-invasive medical imaging technique that uses ultrasound waves to measure blood flow velocity in the major arteries of the brain, specifically within the circle of Willis. The research paper you referenced explores the use of TCCD as a potential measurement modality for BCIs. Quantitative electroencephalogram (qEEG) is a powerful tool for understanding brain function qEEG can reveal specific brain wave patterns associated with drug addiction, potentially providing insights into the neurobiological mechanisms underlying cravings, withdrawal symptoms, and relapse risk in Methamphetamine User Disorder (MUD). There is growing research interest in using Transcranial dopller as a measurement modality for BCIs.Here are some of the key considerations for using Transcranial doppler in BCIs: Mental Tasks, signal processing and classification, accuracy and reliability. Transcranial doppler provides information about blood flow in specific arteries but lacks detailed spatial information about brain activity. These patterns could vary depending on the type of drug, the severity of addiction, and individual differences. Transcranial doppler in measuring middle cerebral artery (MCA) blood flow velocity parameters (peak systolic velocity (PSV) and mean flow velocity (MFV)). qEEG can help researchers investigate the complex interplay between addiction and other brain disorders, like depression or anxiety. Characteristic qEEG in drugs addiction Increased Theta (4-8 Hz) and delta (1-4 Hz) brain waves are often associated with sleep and relaxation. However, research has shown that individuals with drug addiction may have increased theta and delta activity, particularly in the frontal and temporal regions of the brain. Altered Beta (13-30 Hz) brain waves are generally associated with wakefulness, alertness, and cognitive processing. Studies have observed both increases and decreases in beta activity in individuals with drug addiction, depending on the type of drug, the stage of addiction, and the specific brain regions being examined. The results of this research have important practical implications for building an diagnostic and functional assement with a better understanding of an using technology.